Polycarbene-bearing membrane surface containing silver species for size and charge selective molecular separation. Issue 10 (7th September 2022) - Naik, Nagaraj S.; Sherugar, Prajwal; Vishnumurthy, K. A.; Arthanareeswaran, G.; Das, Diganta B.; Padaki, Mahesh
Abstract : A very simple yet powerful strategy is developed for surface modification of poly(ionic liquid)-based membranes under natural sunlight, resulting in improved molecular separation efficiency. Abstract : The separation of narrow-sized molecules through membrane technology is a very tedious task. However, a highly selective molecular separation process can be achieved from hydrophilic membranes with well-defined pores. Herein, we report a blend membrane surface modified with polycarbene stabilized silver species for molecular separation. The excellent separation performance and the high flux of the selective membrane have been attributed to the thin selective layer containing hollow spheres and that is filled with silver nanoparticles, which provide the complete rejection of dyes bearing molecular sizes >1.4 nm. The outstanding separation performance of the surface-modified membranes is due to both Donnan exclusion and adsorption effects. The simple surface-modification strategy for blend membranes is adaptable to a variety of other transition metals. Due to the simple fabrication process and inspiring permeability (>80 L m −2 h −1 ), these membranes are economic for the separation of small molecules with good separation efficiency (>95%).